Evaluating the soybean oil packaging characteristics in Brazilian Midwest region (Research, Society and Development, 2022)
The main goal of this study is to evaluate the influence of soybean oil packaging attributes on consumer preferences in Brazilian Midwest region using Multivariate Data Analysis. Four packaging attributes were evaluated: the presence of additional information on label of packaging, brand (popular and non-popular), type of soybean (genetically modified and non-genetically modified) and shape of the packaging (conventional and innovative). Eight images were evaluated by 400 consumers in Midwest region of Brazil. We used the Conjoint Analysis to analyze and measure the impact of each product attribute in consumer preference. The results show that, in general, the consumers were influenced positively by the presence of additional information, innovative package, popular brand and non-transgenic soybeans. Some groups of individuals could not distinguish or did not care about genetically modified soy. Further studies are recommended to evaluate if consumers have difficulties to interpret the symbols on the packaging label (transgenic or organic, for example), as well as it is necessary to extend this survey to other Brazilian states. The food industry will be able to develop packaging and marketing strategies using consumer profiles. The study is useful for the definition, modification and adaptation of soybean oil products.